2021
DOI: 10.1007/s10706-021-01766-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Performance of Pipe Roof Method Adjacent to the Underground Construction

Abstract: In this paper, the behaviour of the pipe roof method with different pipe roofs disposition schemes including the pipe roof gate system and L-shaped system is discussed in terms of ground settlement reduction in the condition of underground space construction adjacent to the existing structure by using numerical simulation method. Considering the construction sequences of parallel underground tunnels with rectangular cross sections, the appropriate parameters and ground response characteristics of the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Construction of urban underground tunnels, as one of the important solutions, currently faces major technical challenges, such as the safety risks of underpass operating tunnels or existing buildings, tunnel construction in soft soil layers with high water content, and predicting and regulating settlement deformation [4,5]. Tunnel excavation frequently results in the deterioration of rock and soil mass and surface deformation of the project and its surrounding environment, resulting in underground pipeline rupture, serious ground settlement, or even collapse, cracking, and damage to adjacent structures [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Construction of urban underground tunnels, as one of the important solutions, currently faces major technical challenges, such as the safety risks of underpass operating tunnels or existing buildings, tunnel construction in soft soil layers with high water content, and predicting and regulating settlement deformation [4,5]. Tunnel excavation frequently results in the deterioration of rock and soil mass and surface deformation of the project and its surrounding environment, resulting in underground pipeline rupture, serious ground settlement, or even collapse, cracking, and damage to adjacent structures [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The pipe-roof (PR) method is one of the important support methods in the shallow buried excavation construction [1,2]. It uses micropipe jacking technology to jack in steel pipes around the proposed underground building; the steel pipes are connected with locking ports and injected with waterproof materials to form a watertight underground space, and then the next step of soil reinforcement and excavation is carried out under the protection of the pipe roof [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [14] studied the response of roadway and subway tunnel to pipe jacking construction through three-dimensional numerical simulation. Ma et al [15] discussed the influence of construction sequence on the existing structure by numerical simulation. Lavasan a et al [16] found that different backfill grouting simulation methods have little impact on the axial force of lining whereas the longitudinal stiffness of the existing tunnel lining is one of the major factors affecting the deformation.…”
Section: Introductionmentioning
confidence: 99%